La formation de formateurs: identité et professionnalisation. Une analyse a travers un modele systemique sui generis "The Three Dimensional Spiral of Sens" - Aparicio, Miriam Teresita (2018)
In this paper, we deal with the historical-social situation of teacher education in Argentina and those aspects which have led to a so-called “weakened identity” of this education system and of teachers themselves. This allows us to analyze the self-sustained movement between the macrosocial, meso-organizational and microindividual dimensions; feedback that is the base of the author’s systemic model sui generis entitled « The Three Dimensional Spiral of Sense » (The Three Dimensional Spiral of Sense, 2015). This analysis is based on the results of more than thirty years of research in the field with different populations. Here, we first highlight some decisive historical events related to teacher education – inspired by the French system – with their gray areas which are linked to weakened identity at the structural and meso-organizational levels. Secondly, we make reference to the results of the latest French-Argentine comparative study (2014-2016), carried out with teachers from IUFM. Our research has been particularly qualitative and uses the technique of hierarchical evocation, among others. With this technique, we have been able to observe which social representations shared by French and Argentine teachers are at the heart of the issue (nodes) and which are peripheral, that is, less important. We have distinguished many dimensions, categories and sub-categories inside each node. The similarities and differences found illustrate the influence or impact of the macro level – socioeconomic and political – on the meso-institutional and micro levels: conceptions and pathways of PhDs and social factors/pathways to their identities and level of professionalization